Application of Laughter Therapy for the Quality of Life of the Elderly: Literature Review - Freanti, Putri; Susanto, Tantut; Kurdi, Fahruddin (Jurnal Kesehatan Komunitas Indonesia, 2023)
Introduction: The quality of life of the elderly is influenced by two important aspects, namely education and health where around 24% of 100 elderly experience health problems, where aging in the elderly causes a decrease in the body's reserve capacity and an increased risk of disease. One of the therapies that can be used to improve the quality of life of the elderly is namely laughter therapy which is useful in relieving disease symptoms, such as fatigue so as to improve the quality of life of the elderly. Objective: This study aims to identify the laughter therapy application that provides information about concepts and relevant data related to the topic of using laughter therapy in fulfilling the quality of life of the elderly. Method: The design of this study is using a literature review of articles using the search engine database of PubMed, SpringerLink, ScienceDirect, Google Scholar and Wiley Online Library using PRISMA flowchart. Results: The results are showed from this study are that five articles met both the criteria of inclusion and exclusion. After being given by laughter therapy intervention, have a positive impact on reducing symptoms of depression and anxiety which can affect survival in old age related with elderly’s quality of life. Conclusion: This study could conclude that using laughter therapy could increase quality of life of the elderly during aging process included to every aspect such as psychological, physical, social and environmental adaptation.